Asean integration : a work in progress, not an 'illusion' - K. Kesavapany (2015)
ASEAN and its integrative processes are working well, albeit at less than desired speed. However, the real worth and value of ASEAN is the consciousness that has been developed among ministers, officials and NGO representatives of thinking in regional terms.